2020
DOI: 10.1007/s40614-020-00269-5
|View full text |Cite
|
Sign up to set email alerts
|

On the “Strength” of Behavior

Abstract: The place of the concept of response strength in a natural science of behavior has been the subject of much debate. This article reconsiders the concept of response strength for reasons linked to the foundations of a natural science of behavior. The notion of response strength is implicit in many radical behaviorists’ work. Palmer (2009) makes it explicit by applying the response strength concept to three levels: (1) overt behavior, (2) covert behavior, and (3) latent or potential behavior. We argue that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…This study adds to a growing body of evidence challenging behavioral momentum theory (e.g., Bell, 1999; Craig & Shahan, 2016; Grace et al, 1998; Reiss & Bell, 2016). Other research raises broader concerns about the usefulness of the notion of response strength itself, as a theoretical construct (e.g., Simon et al, 2020). For example, some work (e.g., Bell & Williams, 2002; Williams & Bell, 1999) has demonstrated that preference and resistance to change, two putative measures of response strength, do not necessarily covary, as Nevin and Grace (2000) claimed (Grace, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to a growing body of evidence challenging behavioral momentum theory (e.g., Bell, 1999; Craig & Shahan, 2016; Grace et al, 1998; Reiss & Bell, 2016). Other research raises broader concerns about the usefulness of the notion of response strength itself, as a theoretical construct (e.g., Simon et al, 2020). For example, some work (e.g., Bell & Williams, 2002; Williams & Bell, 1999) has demonstrated that preference and resistance to change, two putative measures of response strength, do not necessarily covary, as Nevin and Grace (2000) claimed (Grace, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…I have long been dismayed by the ease with which psychologists invoke explanatory fictions in the interpretation of behavior, so I find myself sympathetic with Simon et al (2020) in their insistence for conceptual clarity. I agree to this extent: the concept of response strength as a hypothetical construct plays no role in the experimental analysis of behavior, at least at our present level of technology.…”
Section: Discussionmentioning
confidence: 99%
“…Sherrington (1906), who is credited with introducing the term "synapse" (Foster & Sherrington, 1897) was aware that synapses differed in their "facility of conduction" (p. 155) and assigned them hypothetical integer values to illustrate how a sensory stimulus might be differentially allocated to various effectors. Simon et al (2020) prefer that the line between behavior and neurophysiology be kept distinct, but they embrace functional explanations at every level and suggest that we supplement our understanding of behavior by reference to evolutionary contingencies. I heartily endorse the latter proposal but not the first.…”
Section: Putting Empirical Meat On the Bones Of The Concept Of Response Strengthmentioning
confidence: 99%
See 2 more Smart Citations